Wilson's Disease (KYAMC Journal, 2017)
Introduction: Wilson's Disease referred to as hepatolenticular degeneration with excessive copper retention involving liver and brain. Hepatic manifestations predominate in children and neuropsychiatric manifestations predominate in adolescents, adults.Case presentation: This is a case report of 24 years old female with long standing difficulty in walking and speech. Computerized tomography imaging showed bilateral symmetrical hypodensity in lentiform nucleus of basal ganglia, thalamus due to copper deposition and slit lamp examination showed Kayser-Fleischer (KF) ring surrounding limbus corneae.Conclusion: Professional counselling and support in addition to drug treatment provide help to patient and her family to overcome their problems and improve the treatment outcome.KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 488-490